1981
DOI: 10.1021/j150611a028
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacities and volumes of the ternary system benzene-water-2-propanol

Abstract: The densities and heat capacities per unit volume were measured over the whole miscibility region of the ternary system benzene-2-propanol-water. From these data, the apparent molal volumes and heat capacities of benzene and water were calculated. These functions for benzene show large changes in the water-rich region while the functions for water change rapidly in the benzene-rich region. In the intermediate range all changes are gradual. These results suggest that microtransitions, which are analogous to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
2

Year Published

1981
1981
1989
1989

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 1 publication
3
14
0
2
Order By: Relevance
“…A denser packing of the molecules results in an increase in the ultrasonic velocity and a decrease in the compressibility of these solutions. This 3~h e supplementary tables may be purchased from (2) in mixtures of ( A ) W-BE (2), (B) BE-BNZ (2), and (C) BE-DEC (2) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A denser packing of the molecules results in an increase in the ultrasonic velocity and a decrease in the compressibility of these solutions. This 3~h e supplementary tables may be purchased from (2) in mixtures of ( A ) W-BE (2), (B) BE-BNZ (2), and (C) BE-DEC (2) …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that microphase structures occur in mixtures of water, alcohol, and oil (1)(2)(3). Water and alcohol mixtures themselves show unique minima and maxima in their thermodynamic properties at low alcohol concentrations (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La nature de l'isopropanol, de par son caractere Itgerernent amphiphile, fait qu'il est susceptible de former des microagrCgats dans l'eau, aussi certains auteurs ont-ils CvoquC le "r61e actif de l'isopropanol dans les micro6mulsions sans detergent" (33,34). Dans les solutions micellaires, l'isopropanol agit a la fois sur la structure du solvant ct sur les proprietts micellaires provoquant un abaissernent de la cmc du tensioactif.…”
Section: Resultsunclassified
“…Incidentally, in recent years, the amount of reliable data on such functions has increased remarkably (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). At the same time, theoretical models have been developed to simulate the trends in the transfer functions and extract, from the data, fundamental thermodynamic parameters for the mixed micelles (18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%